Chromatographic Fingerprint Analysis of Radix Hedysari Using Supercritical Fluid Chromatography Coupled with Diode Array Detector. (4th March 2020) - Wang, Bo; Liu, Xiaohua; Xue, Zhiyuan; Yang, Xiuyan; Fang, Yaoyao; Zhao, Lianggong; Feng, Shilan
Abstract: A newly and rapid supercritical fluid chromatography method for the simultaneous determination of 11 active compounds in Radix Hedysari samples has been developed and validated. Optimum separation was achieved on a HSS SB C18 column with a gradient elution at a flow rate of 1.5 mL/min, back pressure of 11.03 Mpa and diode array detector at 260 nm. The results from the quantitative data showed that contents of these 11 active compounds were different from plant regions. Especially the contents of formononetin in the Minxian county are ~6-fold than in wild Radix Hedysari. The chromatographic fingerprint of Radix Hedysari was recorded under the same chromatographic condition. Data analytic procedure was performed to differentiate the 25 batches of Radix Hedysari samples. Data from chromatographic fingerprint were also analyzed using hierarchical cluster analysis. The results showed that 23 batches of Radix Hedysari samples had a high similarity (> 0.90) and overall 25 batches of sample were divided into two clusters. Moreover, according to the comparison contents of active compounds in each Radix Hedysari samples, the cultivated location of Radix Hedysari was successfully distinguished. This method presented good stability, repeatability and precision and would be a useful and reliable approach for the quality control of Radix Hedysari . Moreover, all target compounds were quantified by ultra-high performance liquid chromatography–time-of-flight mass spectrometry.